Low energy aware communication process in IoT using the green computing approach. Issue 4 (1st July 2018) - Kallam, Suresh; Madda, Rajasekhara Babu; Chen, Chi‐Yuan; Patan, Rizwan; Cheelu, Dhanaraj
Abstract : The Internet of Things (IoT) is a ubiquitous network that interconnects and integrates the devices and cyberspace to enable the smart objects. It lays a platform to collect, process, and to analyse the data for monitoring and controlling the cyber–physical world by using IoT sensor devices. These sensor devices can be wired or wireless that connects to IoT. The wireless devices are battery‐operated devices, unlike wired devices. The energy reduction is critical for battery‐operated devices. The smart devices need an intelligent transmission that increases the life of the devices. There are difficulties in sensor management with regard to energy reduction by applying the energy‐efficient communication energy saved over IoT devices communication. Finally, the low energy aware communication process can enhance device life time in IoT. Least energy aware communication technique is a promising paradigm for IoT is reduced 30% communication overhead.